Blank slate: tactical placemaking strategies as a tool for neighborhood-led activation of vacant lots - Beard, Nicole (Kansas State University, 2023)
A common challenge in disinvested urban areas is a high frequency of vacant land, which directly affects the lives of residents in high-vacancy neighborhoods. The increase of crime, induced fear of crime, and creation of visual blight are potential impacts from urban vacancy (Branas et al. 2018; Hadavi et al. 2021). Reactivating vacant land is an important measure in mitigating the negative consequences of urban vacancy and increasing social cohesion of urban neighborhoods. Tactical placemaking offers interim, programmatic solutions that present low-cost, high-impact approaches to instigating neighborhood change through addressing issues related to safety, equity, and disinvestment (Lak & Kheibari 2020, Finn 2014). Maximum effect of tactical placemaking strategies emanates from an understanding of resident preferences and their capacities towards implementation and maintenance. This study examines tactical placemaking strategies as a neighborhood-led approach to activating vacant lots. Eight high-vacancy neighborhoods in Eastside Kansas City, Missouri were selected as a case to examine residents’ preferences for tactical placemaking strategies and their interest and ability in implementation and maintenance. First, three vacant lot typologies were identified across the study area: enclosed, post-commercial, and wild. Semi-structured interviews were conducted with twenty-seven residents focusing on the type of vacant lot they were most familiar with. The interviews used a participant-generated photo selection activity to understand preferences towards spaces and activities that could be a strategy to reactivate vacant lots. This activity combined with additional questions captured resident preferences towards the potential reactivation strategies, as well as resident willingness and ability to participate in both creating such spaces and maintaining them. Results of the interviews guided a framework of design recommendations specific to each of the three vacant lot typologies. The recommendations include the necessary resources for project construction within four major criteria including time, money, labor, and expertise, while acknowledging how the strategy is expected to activate the space within three areas of opportunity: skill-building, recreation, and gathering. Each recommendation includes a community development rating to further assist community members with decision-making. While providing residents with the foundation for reactivating and reclaiming underutilized land, this study contributes to the literature regarding tactical placemaking and vacancy typologies. The broader implication of this study is that it offers a practical photo-selection method to learn about people’s preferences for outdoor spaces and activities that could be used in community engagement activities.
Keywords: Urban vacancy; Vacant lot reactivation; Tactical placemaking; Preference data; Community development